UNDERGRADUATES’ PERCEPTION OF COMMUNITY SERVICE COURSE-NARRATIVES ON CHALLENGES AND INITIATIVES AT TECHNICAL ENGINEERING UNIVERSITY - Din, Mohd Adri Che; Zin, Mohd Mohamed; Ahmad, Norkhairi bin; Ariffin, Adifarizal Mohd; Ahmad, Noor Kamsiah Che (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2023)
Community service is an important co-curricular course which is offered to university students in many countries to develop critical thinking skills, awareness, empathy and soft-skills like management and communication. How such as course is able to instill in students the desired traits requires more study. This study aims to investigate the perception of undergraduates participating in community service course, the challenges that they have to face and their initiatives as mitigation strategies in achieving the goals of community service. Data for this study is elicited via a simple mix-method approach that combines elements of quantitative and qualitative research. The 68 undergraduates who served as purposive samples were enrolled in a 14-week co-curricular course called community service and were surveyed, interviewed and physically observed as they undertook the assigned tasks. All the community service groups were able to plan and execute four main projects. The study found five types of main challenges that the students have to face namely i. sourcing for funds and financial support, ii. logistics and manpower, iii. group dynamics, communication and cooperation, iv. time management and v. task planning and distribution. Initiatives and mitigation strategies undertaken by the students are having more specific meeting and discussion, exploring all possible options, appointing capable group leader who knows roles well and referring to and consulting lecturers. These insights from this study are useful for tertiary level curriculum planners to further enhance the effectiveness of such experiential learning course to further actualize the potential of the university students.